SISTEM PAKAR UNTUK DIAGNOSA KERUSAKAN KOMPUTER MENGGUNAKAN METODE FORWARD CHAINING DAN CERTAINTY FACTOR BERBASIS WEB - Marpaung, Andy Jhonatan; Handoko, Koko (LPPM Universitas Putera Batam, 2023)
Damage to the computer is caused by several problematic components such as problematic RAM, hard disk or VGA. This condition is a condition of minor damage which sometimes users consider this to be fatal damage due to a lack of knowledge about computer components, which is why an expert system is needed to help users understand. damage to the computer. In this research, the Forward chaining method will be used in the system that will be used in the program. This research will focus on a system that produces and adopts knowledge from an expert in the field and to be able to diagnose computer damage using a web-based method. An expert system is an application that uses the expertise or knowledge of an expert in a particular field and this expertise is implemented in a system.